TRANSFORMASI SISTEM INFORMASI AKUNTANSI DIGITAL MELALUI MANAJEMEN FILE BERBASIS CLOUD BAGI KARANG TARUNA DESA KERTAWANGI - Wulansari, Puspita; Yuliandhari, Willy Sri; Asalam, Ardan Gani; Putra, Muhammad Alrazan Dwiky; Ashfahani, Muhammad Zayyinul Bahri; Putra, Muhamad Alifarizi Dwiangga (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2026)
Digital transformation has become an essential requirement for community organizations to improve the effectiveness of administrative and financial management, including youth organizations such as Karang Taruna of Kertawangi Village, which still face limitations in utilizing cloud-based digital accounting information systems. This activity aims to enhance the understanding and capabilities of Karang Taruna members in managing accounting information systems through cloud-based file management to support more orderly, transparent, and collaborative financial recording and documentation. The community service was conducted through three stages: needs assessment with partners, socialization and training on basic concepts of digital accounting information systems and cloud-based file management, and evaluation through participant feedback. The results show that among the 30 participants involved, the majority of participants gained new understanding regarding the use of cloud-based links for embedding and documenting transaction evidence and gained new understanding of collaborative features, access authorization, and simultaneous document editing using Google Drive. Feedback evaluation indicates a very high level of participant satisfaction regarding the relevance of the material, clarity of delivery, and overall benefits of the activity. In conclusion, this community service program effectively improves digital accounting information system literacy among youth organizations and has the potential to support sustainable financial governance.